2017
DOI: 10.1186/s13023-017-0644-y
|View full text |Cite|
|
Sign up to set email alerts
|

Quantification of gait in mitochondrial m.3243A > G patients: a validation study

Abstract: BackgroundMore than half of the patients harbouring the m.3243A > G mutation were found to have trouble maintaining balance when walking in a recent study by our group. Others demonstrated that these patients had an abnormal gait pattern, as quantified by gait analysis. Gait analysis is an emerging method to quantify subtle changes in walking pattern, also during therapeutic interventions. Therefore, we aimed to test the reliability and reproducibility of gait analysis and select the most suitable protocol for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In recent studies, more than half of the patients harboring the m.3243A>G mutation were found to have trouble maintaining balance when walking. Others demonstrated that these patients had an abnormal gait pattern, as quantified by gait analysis . For this reason, and the observation that gait improved during KH176 treatment in a mitochondrial disease mouse model, gait was chosen as a primary end point .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, more than half of the patients harboring the m.3243A>G mutation were found to have trouble maintaining balance when walking. Others demonstrated that these patients had an abnormal gait pattern, as quantified by gait analysis . For this reason, and the observation that gait improved during KH176 treatment in a mitochondrial disease mouse model, gait was chosen as a primary end point .…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] For this reason, and the observation that gait improved during KH176 treatment in a mitochondrial disease mouse model, gait was chosen as a primary end point. 17,19,20 This 28-day phase IIA study showed no improvement in gait parameters. This can be explained by the fact that 16 of 18 patients participating in this study already had a normal gait at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Upon publication of this article [ 1 ] it was noticed that Table 2 was incorrect. During Production, errors were introduced into the Variable column.…”
Section: Erratummentioning
confidence: 99%
“…The need for relevant animal models that recapitulate the symptoms of a disease is crucial to understand and elucidate the pathomechanisms, and to later use the models to develop therapeutic strategies. Feeding difficulties have frequently been reported in patients with CI deficiencies ( van den Engel-Hoek et al, 2017 ; Kisler et al, 2010 ; Koene et al, 2012 , 2013 ; de Laat et al, 2015 ; Morava et al, 2006 ; Ramakers et al, 2017 ; Read et al, 2012 ; Smeitink, 2003 ), but have largely been neglected in animal models for mitochondrial disease. Here, we present a novel Drosophila model of CI deficiency which develops a dramatic feeding impairment, along with other symptoms recapitulating CI-deficient NDUFS4-mutated patient characteristics, such as a severely reduced lifespan, locomotor defects and signs of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%